Antigen Presentation in the Gut - W Doe; P Pavli (Canadian Journal of Gastroenterology)
The induction of T cell responses requires recognition of antigens in association with class II major histocompatibility complex (MHC) proteins and specialized antigen-presenting cells. Candidate antigen-presenting cells in the gut include dendritic cells, macrophages, B lymphocytes, mucosal epithelial cells and endothelial cells. Dendritic cells isolated from normal human colon are potent inducers of primary immune responses and express high levels of class lI MHC proteins. Lamina propria macrophages display class II MHC proteins, can present antigens to sensitized T cells, may process antigen and release interleukin-l, but suppress antigen presentation by intestinal dendritic cells in a dose-dependent manner. Class II MHC molecules are normally expressed on small intestinal epithelial cells but not on normal colonic epithelial cells. Suppressor T cells and unresponsive T helper cells in the mucosa appear to mediate systemic T cell tolerance of dietary antigens. In the inflamed colon there is infiltration of the lamina propria by large numbers of monocytes which secrete interleukin-1, and the release of interferon-gamma appears to induce class II protein expression on colonic epithelial cells. Colonic epithelial cells from inflamed bowel may preferentially stimulate T helper cells so that local induction of class II MHC molecules on epithelial cells may amplify and localize secondary immune responses at the site of inflamed mucosa. Taken together, the aberrant expression of class II MHC molecules, breaches in epithelial cell integrity (resulting m exposure to luminal antigens including endotoxin and the increased numbers of monocytes found 10 inflamed mucosa suggest that the resulting distortions in antigen presentation contribute to the localization and persistence of the inflammatory lesion in inflammatory bowel disease.